Mediation in the Religious Courts of Indonesia - Karmawan Karmawan (AHKAM : Jurnal Ilmu Syariah, 2020)
This study discusses mediation in civil law cases in the Indonesian Religious Courts as a mean to solve the court congestion problem. This is a normative legal study and aims at analyzing the implementation of Supreme Court Regulation No. 1 of 2016 in the Religious Courts. In practice, agreements resulted from mediation will be ratified by a mediator and have similar legal consequences as judges’ decisions. This, in turn, helps the court reducing the number of cases brought before the court. This study argues that the success of mediation relies on mediators’ professionalism and legal culture in society. The success is also shown by the number of agreements issued as the result of mediation. AbstrakKajian ini membahas efektifitas mediasi dalam kasus perdata di Pengadilan Agama di Indonesia. Dengan menggunakan pendekatan studi hukum normatif, artikel ini bertujuan untuk menganalisis implementasi PERMA No. 1/ 2006 tentang Mediasi di Pengadilan Agama. Mediasi diyakini dapat menjadi solusi untuk mengurangi jumlah kasus yang dibawa ke pengadilan, karena dengan mediasi berbagai sengketa hukum dapat diselesaikan tanpa litigasi. Kesepakatan yang dihasilkan dalam proses mediasi akan dicatat oleh mediator dan memiliki konsekuensi hukum yang sama dengan putusan hakim. Kajian ini menyimpulkan bahwa lembaga peradilan di Indonesia perlu berupaya secara serius untuk mengoptimalkan mediasi dan memberikan keadilan melalui mediasi.